Religious and Cultural Integration in the Baayun Mulud Tradition of the Banjar Tribe - Lina Amiliya; Nasrudin; Bakri, Zulfikarni (LP2M UIN Sunan Kalijaga, 2023)
The concept of integration between religion and culture is capable of producing new religious mosaics with local characteristics. As is the case with the Baayun Mulud Tradition from the Banjar Tribe, from a cultural context, the Baayun Mulud Tradition is a religious practice that is thick with the integration of Islamic values. This study uses a qualitative approach with data collection techniques such as interviews, observations, and literature based on relevant studies. The results of this study indicate that there is integration between religion and culture in the Baayun Mulud Tradition. The presence of Islam was able to change traditions that were originally closely related to the spirit of the unseen world into traditions that have Islamic elements, such as reciting shalawat poems addressed to the Prophet Muhammad. Meanwhile, culture is a form of practice for several Islamic values. [Konsep integrasi antara agama dan budaya mampu melahirkan mozaik-mozaik keagamaan baru yang berwatak dan bercorak lokal. Seperti halnya yang terjadi pada Tradisi Baayun Mulud dari Suku Banjar. Dari konteks budaya, Tradisi Baayun Mulud menjadi praktik keagamaan yang kental dengan integrasi nilai-nilai keislaman. Kajian ini menggunakan pendekatan kualitatif dengan tekhnik pengumpulan data wawancara, observasi serta studi pustaka berdasarkan kajian yang relevan. Hasil penelitian ini menunjukkan bahwa terjadi integrasi antara agama dan budaya pada Tradisi Baayun Mulud. Hadirnya agama Islam mampu merubah tradisi yang awalnya erat dengan ruh alam ghaib menjadi tradisi yang mempunyai unsur-unsur keIslaman seperti pembacaan syair-syair shalawat yang ditujukan kepada Nabi Muhammad. Sedangkan budaya menjadi wujud praktik dari beberapa nilai keislaman.]